Resilience and Work Stress in Educational Institutions of Chepén, 2024: Mediation of Motivation and Time Moderation - Abigail Silvia Jara Cerdan; Rosa Jackeline Medina Sanchez; Marco Agustín Arbulú Ballesteros (Behavioral Sciences)
The purpose of this study was to examine the relationship between resilience and work-related stress among secondary school teachers in Chepén, Peru, during 2024, with a focus on (a) the mediating role of work motivation and (b) the moderating effect of years of service. Using a non-experimental quantitative design, data were collected from 450 teachers and analyzed in SPSS 27 with Hayes’ PROCESS 4.3 macro. Results showed that resilience significantly predicted motivation (β = 0.413, p < 0.001), accounting for 35% of its variance (R2 = 0.35). In turn, motivation was significantly and negatively associated with work stress (β = 0.335, p = 0.0401), explaining 20% of the variance in stress levels (R2 = 0.20). Neither resilience (β = 0.187, p = 0.5420) nor years of service (β = 0.217, p = 0.9003), nor their interaction (β = 0.002, p = 0.8144) had a direct or moderating effect on work stress. Descriptive analyses indicated that most teachers exhibited moderate levels of resilience (51.1%), stress (42.2%), and motivation (37.8%). These findings underscore that resilience alone does not reduce work stress; its stress-buffering effect operates through enhanced motivation. Educational interventions should therefore target both resilience-building and motivational strategies to effectively diminish teacher stress and promote occupational well-being.